Different morphological structures of breast tumors demonstrate individual drug resistance gene expression profiles - Gerashchenko, T.S.; Denisov, E.V.; Novikov, N.M.; Tashireva, L.A.; Kaigorodova, E.V.; Savelieva, O.E.; Zavyalova, M.V.; Cherdyntseva, N.V.; Perelmuter, V.M. (Experimental Oncology, 2018)
Aim: To identify gene expression profiles involved in drug resistance of different morphological structures (tubular, alveolar, solid, trabecular, and discrete) presented in breast cancer. Material and Methods: Ten patients with luminal breast cancer have been included. A laser microdissection-assisted microarrays and qRT-PCR were used to perform whole-transcriptome profiling of different morphological structures, to select differentially expressed drug response genes, and to validate their expression. Results: We found 27 differentially expressed genes (p < 0.05) encoding drug uptake (SLC1A3, SLC23A2, etc.) and efflux (ABCC1, ABCG1, etc.) transporters, drug targets (TOP2A, TYMS, and Tubb3), and proteins that are involved in drug detoxification (NAT1 and ALDH1B1), cell cycle progression (CCND1, AKT1, etc.), apoptosis (CASP3, TXN2, etc.), and DNA repair (BRCA1 and USP11). Each type of structures showed an individual gene expression profile related to resistance and sensitivity to anticancer drugs. However, most of the genes (19/27; p < 0.05) were expressed in alveolar structures. Functional enrichment analysis showed that drug resistance is significantly associated with alveolar structures. Other structures demonstrated the similar number (10–13 out of 27) of expressed genes; however, the spectrum of resistance and sensitivity to different anticancer drugs varied. Conclusion: Different morphological structures of breast cancer show individual expression of drug resistance genes. Key Words: breast cancer, tumor heterogeneity, gene expression, chemotherapy, drug resistance.